Factors of Services Quality in Malaysian Private Higher Education Institutions and Its Relation to Consumer Satisfaction - Md Ghazali, Faizah (2008)
Malaysia’s Private Higher Education sector is one of the major contributors to the economy of Malaysia and is a catalyst in the development of human capital. However, feedbacks received from students pertaining to quality issues among Private Higher Education Institution (PHEI) has raised concerns on services quality rendered by PHEI. The focus of quality in services is to fulfill the needs and wants of consumer. Very often, aspects considered as quality from PHEI’s management perspective might not be able to fulfill the needs and wants of students. Hence, this research focuses on the evaluation of services quality from the students’ perspective as consumers of PHEI. The study aims to identify service quality factors in PHEI and factors which influenced student satisfaction as consumers of PHEI. The research instrument was based on disconfirmation theory for the purpose to gauge services quality in terms of students’ expectations. A total of 325 respondents from two private universities formed the samples in the study. Five factors of services quality have been identified through factor analysis. They were, programme of studies, service facilities, lecturers’ empathy, lecturers’ expertise and physical environment. Finding showed that quality factor attributed to programme of studies as perceived by students, ranked the highest in terms of mean score (M=5.10, SD=0.88) at 7-point scale while the factor of service facilities ranked the lowest (M=4.09, SD=1.29). Even though the programme of studies was perceived by students to be of the highest quality, however physical environment had a substantial impact on students’ satisfaction (β=.291, p<.01). Findings also showed there was a significant difference in students’ level of perception towards services quality in terms demographic aspects; field of studies [F(2,322)=14.945, p<.01], sponsorship of studies [F(2,322)= 11.680, p<.01] and type of students’ residence [F(2,322)=18.127, p<.01] while there was no significant difference in terms of students’ level of perception towards services quality on the aspects of gender, race and year of studies. Findings showed there was significant difference in consumer level of satisfaction in the aspects; field of studies [F(2,322)= 9.502, p<.01], sponsorship of studies [F(2,322)= 7.001, p<.01], year of studies [F(2,322)= 3.713; p<.05] and type of students’ residence [F(2,322)= 4.301, p<.05] while there was no significant difference in consumer level of satisfaction on the aspects of gender and race. The study concludes; physical environment factor should be given emphasis to ensure service quality rendered by PHEI is able to fulfill students’ satisfaction.